PENGARUH GAYA KEPEMIMPINAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN DI BANK NAGARI KOTO BARU KABUPATEN DHARMASRAYA - Anggraini, Widya; Kencana, Anggia Putri (Media Mahardhika, 2025)
This research is motivated by employee performance caused by leadership style and training at Nagari Koto Baru bank, Dharmasraya Regency. The purpose of this study was to determine the effect of leadership style and training on employee performance at Nagari Koto Baru bank, Dharmasraya Regency. The method used in this research is descriptive quantitative. Data collection techniques by distributing questionnaires to 50 respondents measured by a Likert scale. The analysis technique uses multiple linear regression analysis with the help of SPSS 21 then described descriptively. The results showed that (1) there is an influence of leadership style on employee performance as evidenced by the t value of the leadership style variable count greater than the t table of 6.948>2.011 or a significance level smaller than 0.05; (2) there is an influence of training on employee performance as evidenced by the t value of the training variable count greater than the t table of 3.953>2.011 or a significance level smaller than 0.05.